POTENSI PENGEMBANGAN OBJEK WISATA PEMANDIAN AIR PANAS SUNGAI PINANG KECAMATAN HULU KUANTAN KABUPATEN KUANTAN SINGINGI - ", Riskiati; Sidiq, Siti Sofro (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Hot spring water bathing is one of the attraction in Kuantan Singingi Regency. This Study aims to determine the potential and inhibiting factors of the potential development of hot spring bathing attraction in the Sungai Pinang, Hulu Kuantan District, Kuantan Singingi Regency. This study uses descriptive quantitative methods. The sample in this study were 98 respondents, determining respondents with incidental sampling. Data collection techniquest used are observation, interview, questionnaire and documentation using the Likert scale as a measuring instrument. Based on the results of research, the potential development of hot water bathing attraction in Sungai Pinang, Hulu Kuantan Subdistrict, Kuantan Singingi Regency with sub-variabels of tourist attraction and attraction, tourism infrastructure, tourism facilities, infrastructure management and community and environment with a good research conclusionkeywords : Potential, Development, Attraction